Identification of the mass-silent post-transcriptionally modified nucleoside pseudouridine in RNA by matrix-assisted laser desorption/ionization mass spectrometry - Patteson, K. G. (Oxford University Press, 2001)
A new method using matrix-assisted laser desorption/ionization (MALDI) mass spectrometry for the direct analysis of the mass-silent post-transcriptionally modified nucleoside pseudouridine in nucleic acids has been developed. This method utilizes 1-cyclohexyl-3-(2-morpholinoethyl)carbodiimide to derivatize pseudouridine residues. After chemical derivatization all pseudouridine residues will contain a 252 Da ‘mass tag’ that allows the presence of pseudouridine to be identified using mass spectrometry. Pseudouridine residues can be identified in intact nucleic acids by obtaining a mass spectrum of the nucleic acid before and after derivatization. The mass difference (in units of 252 Da) will denote the number of pseudouridine residues present. To determine the sequence location of pseudouridine, a combination of enzymatic hydrolysis and mass spectrometric steps are used. Here, MALDI analysis of RNase T1 digestion products before and after modification are used to narrow the sequence location of pseudouridine to specific T1 fragments in the gene sequence. Further mass spectrometric monitoring of exonuclease digestion products from isolated T1 fragments is then used for exact sequence placement. This approach to pseudouridine identification is demonstrated using Escherichia coli tRNAs. This new method allows for the direct determination of pseudouridine in nucleic acids, can be used to identify modified pseudouridine residues and can be used with general modification mapping approaches to completely characterize the post-transcriptional modifications present in RNAs.